From technological to social innovation: toward a mission-reorientation of entrepreneurial universities - Matthias Menter (The Journal of Technology Transfer, 2023)
Social innovation has increasingly become an issue of policy and particularly given the policy focus on societal grand challenges. As anchor institutions, the challenge for entrepreneurial universities is to effectively respond and contribute to both technological and social innovation through knowledge and technology transfer. The current conceptualization of entrepreneurial universities is predominately focused on technological innovation. This paper argues for a mission-reorientation of entrepreneurial universities that extends the current technological innovation based conceptualization to incorporate social innovation that effectively addresses environmental and societal challenges and responds to calls in the society for more sustainable and inclusive growth. While current business models that underpin entrepreneurial universities and underlying knowledge and technology transfer mechanisms mainly incentivize the commercialization and transfer of economic knowledge, an incorporating of social dimensions of innovation allows the conceptualization of a broader and more extensive role of entrepreneurial universities.
Keywords: O30; O35; 600; Entrepreneurial university; University mission; University business model; Social innovation; Technological innovation; Public sector entrepreneurship